Pengaruh Kepemimpinan Otentik, Psychological Capital, dan Kepuasan Kerja terhadap Komitmen Organisasi Guru di SMP dan SMA XYZ Cikarang - Wibhawa, Martinus Ronny (Jurnal Ketopong Pendidikan, 2023)
Schools must pay close attention to teachers’ organizational commitment, as teachers with strong commitment tend to be loyal, responsible, and actively contribute to achieving the school’s goals. This study aims to examine the effect of job satisfaction, authentic leadership, and psychological capital on teachers’ organizational commitment at Middle School XYZ Cikarang. The research involved forty-one teachers as respondents and employed a quantitative approach using the path analysis method. Data were collected through a questionnaire based on a Likert scale and analyzed using descriptive and inferential statistical techniques. The findings reveal that the levels of organizational commitment, job satisfaction, authentic leadership, and psychological capital among teachers at Middle School XYZ Cikarang are relatively high. Furthermore, the results indicate that job satisfaction, authentic leadership, and psychological capital jointly explain teachers’ organizational commitment with an R-square value of 0.367. Meanwhile, job satisfaction can be explained by authentic leadership and psychological capital with an R-square value of 0.618. These results suggest that authentic leadership and psychological capital play important roles in enhancing teachers’ job satisfaction, which in turn strengthens their organizational commitment. Therefore, school leaders are encouraged to foster authentic leadership practices and develop teachers’ psychological capital to improve organizational commitment.